(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Routing in MANET is a challenging task due to the dynamic nature of the participating nodes in MANET. This challenge has led to the development of many different routing protocols, with each originator claiming that his or her proposed protocol was more effective than its predecessors were. Nonetheless, the effectiveness of these protocols relies on the prevailing network scenarios, which differ in terms of node density and traffic. Against this challenging backdrop, the authors provide an overview of the different MANET protocols, such as OLSR, AODV, DSR, DSDV, ZRP and TORA, which are broadly classified based on three categories, namely Proactive (table-driven), Reactive (on-demand) and Hybrid routing protocol. The authors then provide a comparative analysis of the different protocols based on qualitative metrics. This paper concludes by highlighting the expected performance of each protocol for a particular network environment, which is deemed suitable based on the specific characteristics of the protocol.